Perencanaan dan Perancangan Aquarium Megatank di Kawasan Pantai Amed Kabupaten Karangasem, Bali - I Made Rama Sukma Pramana; I Nyoman Nuri Arthana; I Ketut Sugihantara (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2022)
Karangasem Regency is one of the regencies that has many beautiful natural attractions from the mountains to the underwater, it is evident that many local and foreign tourists visit Karangasem Amed. This Megatank Aquarium is a facility that can overcome problems related to the arrangement and decline of the ecosystem. underwater biota. By making a conservation effort with aspects of preservation, protection, and utilization, utilization is a conservation effort that becomes an attraction and new innovation related to tourism and for the sustainability of the Indonesian underwater biota ecosystem, especially in the Amed coastal area. With facilities consisting of a Marine Aquarium, Deep Sea Aquarium, Coral Reef Aquarium, Touch Pool, Snorkeling Pool, and many more. This Megatank Aquarium has the concept of "Environment and Technology" which means that marine biota ecosystems develop even though inside buildings with this technology can help for development without having to damage the environment, especially underwater biota. With the theme of Eco-Tech Architecture in environmentally friendly buildings with the utilization of natural potential.